2021
DOI: 10.3390/buildings11110520
|View full text |Cite
|
Sign up to set email alerts
|

Combined Flexural and Shear Strengthening of RC T-Beams with FRP and TRM: Experimental Study and Parametric Finite Element Analyses

Abstract: Due to inadequacies of reinforcement design in older structures and changes in building codes, but also the change of building use in existing structures, reinforced concrete (RC) beams often require upgrading during building renovation. The combined shear and flexural strengthening with composite materials, fibre-reinforced polymer sheets (FRP) and textile reinforced mortars (TRM), is assessed in this study. An experimental campaign on twelve half-scale retrofitted RC beams is presented, looking at various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Thus, gluing the tape to the lower face of the RC beam contributes to absorbing blast energy, while the use of diagonal tapes on the side face of beams and U-shaped systems allows to increase shear strength (Jahami et al, 2021). Detailed experimental study, dedicated to assessment of combined shear and bending reinforcement systems using fiber-reinforced polymer (FRP) and textile reinforced mortar (TRM) composite materials confirmed the increase in shear load-bearing capacity and other parameters of behavior under loading (Pohoryles et al, 2021). This was also confirmed by study of Abdalla et al, who indicated a significant increase in the load-bearing capacity for bending and shear when using composite tapes for wrapping RC beams in combination with rod anchors (Abdalla et al, 2022).…”
Section: Composition and Application Of Frp Materialsmentioning
confidence: 85%
“…Thus, gluing the tape to the lower face of the RC beam contributes to absorbing blast energy, while the use of diagonal tapes on the side face of beams and U-shaped systems allows to increase shear strength (Jahami et al, 2021). Detailed experimental study, dedicated to assessment of combined shear and bending reinforcement systems using fiber-reinforced polymer (FRP) and textile reinforced mortar (TRM) composite materials confirmed the increase in shear load-bearing capacity and other parameters of behavior under loading (Pohoryles et al, 2021). This was also confirmed by study of Abdalla et al, who indicated a significant increase in the load-bearing capacity for bending and shear when using composite tapes for wrapping RC beams in combination with rod anchors (Abdalla et al, 2022).…”
Section: Composition and Application Of Frp Materialsmentioning
confidence: 85%
“…The existing civil infrastructure, like buildings, bridges and marine structures, often require repair and strengthening for various reasons. The various reasons for the repair and strengthening are (i) aging of infrastructure, (ii) corrosion and deterioration due to extreme environmental conditions, 1,2 (iii) damage due to accidental loading such as impact and blast, 3,4 (iv) upgradations due to change in use and additional loading requirements, 5–7 (vi) seismic strengthening and retrofitting 8–10 and (vii) address the defects in design and execution. The fiber‐reinforced polymer (FRP) composites have been widely adopted for the strengthening of reinforced concrete (RC) elements over the last few decades 11–14 .…”
Section: Introductionmentioning
confidence: 99%
“…An extensive number of existing reinforced concrete structures are persistently exposed to damage induced by the deterioration of concrete, natural environmental effects, and corrosion of steel. This might be attributed to the continuous increase in the load requirements compared to what they were originally designed for, the change in the structure's function, and the necessity to meet the current design standards [1]. Repair and strengthening would be an efficient or economical option instead of removing all these structures and replacing them with new ones [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Span length; 2 web width; 3 flange width; 4 web height; 5 flange height; 6 shear span-to-depth ratio.…”
mentioning
confidence: 99%